A new PSFB converter-based inverter arc welding machine with high power density and high efficiency - Aksoy, Ismail (Tubitak Scientific & Technological Research Council Turkey, 2014)
In this study, a high-performance single-phase inverter arc welding machine is presented. Power control of the developed welding machine is realized with a high-frequency, phase-shifted full bridge (PSFB) pulse-width modulation (PWM) converter. The PSFB PWM converter operates with soft switching at no load and full load. There is no need to use a passive snubber in the converter. Welding machine control is implemented with a digital signal processor (DSP) and phase-shift PWM IC. By means of the DSP, advanced arc welding functions and protection features such as short-circuit, over-current, and temperature protection are achieved. The current and voltage waveforms given are from an IGBT-based PSFB PWM arc welding machine operating at 75 kHz switching frequency and 160 A output current. The experimental results show that the proposed system has promising feasibility in industrial applications.
Keywords: Arc welding machine; PSFB PWM converter; DC-DC converter; soft switching; zero-voltage transition; zero-voltage switching; IGBT; ZERO-VOLTAGE; DESIGN CONSIDERATIONS; PWM CONVERTER; FULL; KW; Computer Science; Engineering